Cigarette Smoking among Male Teenagers in Malaysia ? A Narrative Review - R.III P Dioso (Universitas Gadjah Mada, 2014)
This narrative review of a contemporary healthcare issue focuses on strategies and healthcare initiatives to curtail the increasing prevalence of active cigarette smoking among male teenagers in Malaysia — a mission of the Malaysian Millennium Development Goal and the United Nations Development Programmes on all health sectors. This narrative review analysed global and Malaysian views on cigarette smoking.